Dynamics of container cranes: three-dimensional modeling, full-scale experiments, and identification. (April 2015) - Arena, A.; Casalotti, A.; Lacarbonara, W.; Cartmell, M.P.
Abstract: A three-dimensional modeling of container cranes subject to wind loads is presented together with full-scale experimental tests, system identification and model validation. The container is modeled as a rigid body elastically suspended from the trolley running along rails on top of the crane boom and the girder. Differences are discussed with respect to a constrained model, in which the cables are unstretchable. Experimental investigations are carried out on a full-scale container crane and the modal characteristics together with the damping coefficient are identified as a function of the container height. Moreover, the nonlinearities induced by large-amplitude oscillations involving some of the modes are highlighted both in the context of numerical simulations and experimental tests. Time integration is carried out to validate the mechanical model by comparing its predictions with the experimental results. Typical working maneuvers together with the effects of wind-induced loads are taken into account to study the three-dimensional crane response. Abstract : Highlights: Three-dimensional models of container cranes subject to wind loads are proposed. Differences between rigid and elastic hoisting cables models are highlighted. Experimental investigations are carried out on full-scale container cranes. The model correctly predicts the nonlinear behavior due to large oscillations. Damping properties are influenced by the container size and hoisting cables' length.